ST-segment elevation myocardial infarction in a young male patient with polyarteritis nodosa - (:unkn) unknown (My University, 2013)
Treatment of myocardial infarction (MI) caused by vasculitis is not clear yet and prognosis is relatively poor. We report a 21-year old patient with polyarteritis nodosa (PAN), who was presented with acute MI. Despite aggressive medical and interventional therapy including thrombolytic, antiplatelets and rescue percutaneous transluminal coronary angioplasty, the patient died. Our aim is to draw attention to the importance of aggressive treatment and associated complications in these patients.
Keywords: Acute coronary syndrome; Coronary artery disease; Myocardial infarction; Polyarteritis nodosa; Vasculitis